Design Of A 200watts, 12volts Output Voltage Buck-Boost DC-DC Converter For Photovaltaic Application - Lau, Phooi San (Universiti Sains Malaysia, 2005)
Solar energy becomes a very important source of power energy as the other power sources especially petroleum is decreasing. This brings to development of photovoltaic applications. To widen the usage of photovoltaic application, buck-boost converter is an important device to stabilize performance of photovoltaic application that is depends on intensity of the sunshine. A buck-boost converter with 200W and 12V DC output voltage has been designed in this project to help in mentioned problem. This project included design of buck-boost converter, simulation of the circuit and building of hardware. SG 3524 is selected as the SMPS controller for the buck-boost converter. To generate square-wave from SG 3524, simple control circuit had to be designed and connected to the chip. Two types of switch, which are MOSFET and BJT, have been used to decide the most suitable configuration to drive a buck-boost converter. From experiments, PNP BJT is chosen as switch and drives the converter successfully. The output meets expected 12V DC output from varying input between 6V and 20V. Efficiency of this converter is varying between 91% and 47% depends on the varying input voltage. With this buck-boost converter, the input voltage can be stabilized at level 12V by controlled of duty cycle of switching waveform.